Remaja dan Budaya Konsumen pada Iklan Operator Telekomunikasi Seluler Axis - Novita Dwi Wulandari (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The youth and the consumer culture practices stick to Axis advertisement version #BikinBanyakCerita Bareng Axis! The aim of this research is to investigate how the youth and the consumer culture practices are shown on this advertisement. The method is qualitative with a critical perspective and Semiotics from Roland Barthes as the analytical tool. The result is that the youth is symbolized as an individual who is very consumptive towards activity. The youth consume objects consisting of consumption of activity objects and place objects. These objects are not only of use value, but also have symbolic values as a form of identity attached to adolescents. The advertisement also shows the consumer culture of youth from the upper middle class social and in the end used as a commodity by advertisers.